Quince Duncan's Weathered Men and The Four Mirrors Two Novels of Afro-Costa Rican Identity - Mosby, Dorothy E. (Afro-Latin@ Diasporas, 2018)
Quince Duncan is one of the most significant yet understudied Black writers in the Americas. A third-generation Afro-Costa Rican of West Indian heritage, he is the first novelist of African descent to tell the story of Jamaican migration to Costa Rica. Duncan's work has been growing in popularity among scholars and teachers of Afro-Latin American literature and African Diaspora Studies. This translation brings two of his major novels to English-speaking audiences for the first time, Weathered Men and The Four Mirrors. The book will be invaluable for those eager to develop further their background in Afro-Latin American literature, and it will enable students and faculty members in other fields such as comparative literature to engage with the burgeoning area of Afro-Latin American literary studies.